2012
DOI: 10.1136/heartasia-2012-010130
|View full text |Cite
|
Sign up to set email alerts
|

LDL particle heterogeneity, and its association with other established cardiovascular risk factors in a young Indian industrial population

Abstract: Objective Low density lipoprotein (LDL) particles are heterogeneous in terms of size, density, chemical composition and electric charge with certain particle of LDL being more atherogenic than the others. The present study aimed to look at the LDL particle heterogeneity, particle size and association with other cardiovascular disease (CVD) risk factors in young Indian industrial population. Methodology 600 employees of an industry of Delhi, aged 20-39 years were selected for the study. Data on demographics, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
2
1
0
Order By: Relevance
“…Also, Notarnicola et al [ 30 ] showed that higher concentrations of sdLDL would increase the risk of mortality in patients with CVDs. In line with the two studies mentioned, other studies reported similar results [ 24 , 25 , 31 – 34 ]. Further, some studies have specifically examined the association between LDL subtypes and the incidence of various cardiovascular diseases.…”
Section: Resultssupporting
confidence: 87%
“…Also, Notarnicola et al [ 30 ] showed that higher concentrations of sdLDL would increase the risk of mortality in patients with CVDs. In line with the two studies mentioned, other studies reported similar results [ 24 , 25 , 31 – 34 ]. Further, some studies have specifically examined the association between LDL subtypes and the incidence of various cardiovascular diseases.…”
Section: Resultssupporting
confidence: 87%
“…Also, Notarnicola et al (30) showed that higher concentrations of sdLDL increase the risk of mortality in patients with CVDs. In line with the two studies mentioned, other studies reported similar results (24,25,(31)(32)(33)(34). Also, some studies have speci cally examined the association between LDL subtypes and the incidence of various cardiovascular diseases.…”
Section: Characteristics Of the Included Studiessupporting
confidence: 71%
“…However individuals with LDL-C levels within the normal range can also develop atherosclerosis and CVD (61) . This variation in risk is thought to be due to the heterogeneity of these LDL particles with regards to their size, density and chemical composition (62) . Higher concentration of small, dense LDL-P is associated with an increased risk of CVD, independent of overall LDL-C levels (63) .…”
Section: Traditional V Newer Risk Markers Of Cvdmentioning
confidence: 99%